Post‐transplant mortality and graft failure after induction immunosuppression among Black heart transplant recipients in the United States. Issue 11 (8th July 2022) - Salia, Soziema; Mostofsky, Elizabeth; Gupta, Suruchi; Lehman, Laura; Barrera, Francisco J.; Liou, Lathan; Motiwala, Shweta R.; Mittleman, Murray A.
Abstract : Black heart transplant recipients are more likely to receive induction immunosuppression compared to other races because of higher rates of acute rejection, graft failure, and mortality. However, it is not known whether contemporary induction immunosuppression improves their post‐transplant outcomes. To evaluate whether Black patients who were prescribed induction immunosuppression therapy have lower all‐cause mortality or graft‐failure rates compared to those who were not, we studied Black U.S. adult heart transplant recipients in the Scientific Registry of Transplant Recipients database (2008–2018). We used multivariable Cox proportional hazards regression analysis to compare the hazards of all‐cause mortality or graft failure as a composite, for patients who were prescribed induction immunosuppression and those who were not. Among 5160 recipients, 2787 (54.0%) were prescribed induction immunosuppression and 2373 (46.0%) were not. There was no evidence of survival differences according to induction immunosuppression for the composite of all‐cause mortality or graft failure (aHR = 1.13, 95% CI 0.96–1.32), mortality (aHR = 1.14, 95% CI 0.97–1.34), graft failure (aHR = 1.05, 95% CI 0.82–1.34) and acute rejection (aHR = 1.00, 95% CI 0.89–1.12). Given the side effects of treatment, future guidelines should reconsider the recommendation for induction immunosuppression among Black patients. Abstract : Data from the Scientific Registry of Transplant Recipients shows that, among Black heart transplant recipients, rates of all‐cause mortality, graft failure, and acute rejection are similar for patients who received or did not receive induction immunosuppression.